Provincial and Territorial Government Contributions to the Development of Francophone Minority Communities: Assessment and Projections - Bourgeois, Daniel; Denis, Wilfrid; Dennie, Donald; Johnson, Marc L. (Canadian Institute for Research on LInguistic Minorities, 2007)
For more than forty years, the governments of the nine provinces and three northern territories that are majority Anglophone have been striving to promote the language and culture of their Francophone minority and thereby contribute to its development. Indeed, despite the importance of the federal government contribution, sectors such as education, health, and social and municipal services that are areas of exclusive provincial and territorial jurisdiction contribute to the vitality of Francophone communities. The lack of literature on provincial and territorial action in the area of official languages might lead one to think that such action is rare, or even non-existent, or that it is aimed at inhibiting the development of Francophone communities. It is nothing of the sort. Compilation and analysis of provincial and territorial actions in the area of official languages were thus required. It was necessary first to identify the nature of these actions and compile a list of them, and second to assess them critically. We then proposed a few immediate and long-term projections. The research covered nine sectors of activity: 1) public communications and services, 2) early childhood development, 3) health and well-being, 4) justice, 5) arts and culture, 6) economic development, 7) target groups (youth, seniors, and women), 8) immigration and 9) municipalities. The section on Health and Well-being discuss 6 themes: a) Legislation and Case Law; b) Policy; c) Programs and Services; d) Publications and Other Documents; e) Financial Support and Institutionalization; f) Training.

Comparaisons internationales : un aperçu de l'accès aux soins de santé pour les communautés de langue officielle en situation minoritaire au Canada, en Espagne, en Belgique et en Finlande - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Programme de contribution pour l'amélioration de l'accès aux services de santé pour les communautés de langue officielle en situation minoritaire. Évaluation formative. - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

Profil des ressources des communautés francophones en milieu minoritaire - Deroche, Francine; Simard, Anne; Di Ruggiero, Erica; Levesque, Johanne (Reflets, 2007)
Le Réseau canadien de la santé (RCS) est une initiative nationale financée par Santé Canada. Le Réseau favorise l’accès à une information fiable, crédible et continuellement mise à jour, sur la santé et vient renforcer les réseaux existants de promotion de la santé. Le RCS a mené une enquête pour identifier quelles sont les informations disponibles sur la santé dans les communautés francophones vivant en milieu minoritaire. Il s’agit là d’un point de départ pour permettre au RCS de planifier et de mettre en œuvre des services en français pertinents. Les objectifs de l’enquête étaient: • d’identifier et d’établir le profil des organismes qui traitent de la santé des Francophones; • d’identifier les types d’organismes recommandés comme sources d’information aux consommateurs et consommatrices et aux intermédiaires de la santé; • d’identifier les ressources existantes les plus souvent demandées par les consommateurs et consommatrices et les intermédiaires de la santé et, • d’identifier les lacunes en matière d’informations sur la santé des francophones

La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. - Official Language Community Development Bureau (Health Canada, 2007)